Vyshnivetsky Castle Library of Prince Mychailo Servaty Vyshnivetsky – Historical Book Heritage and Object of Bibliological and Historical Reconstruction - Tsiborovska-Rymarovych, Iryna (Bibliotheca Lituana, 2014)
The article has as its object the elucidation of the history of the Vyshnivetsky Castle Library, definition of the content of its fund, its historical and cultural significance, correlation of the founder of the Library Mychailo Servaty Vyshnivetsky with the Book. The Vyshnivetsky Castle Library was formed in the Ukrainian historical region of Volyn’, in the Vyshnivets town – “family nest” of the old Ukrainian noble family of the Vyshnivetskies under the “Korybut” coat of arm. The founder of the Library was Prince Mychailo Servaty Vyshnivetsky (1680–1744) – Grand Hetman and Grand Chancellor of the Grand Duchy of Lithuania, Vilno Voievoda. He was a politician, an erudite and great bibliophile. In the 30th–40th of the 18th century the main Prince’s residence Vyshnivets became an important centre of magnate’s culture in Rich Pospolyta. M. S. Vyshnivetsky’s contemporaries from the noble class and clergy knew quite well about his library and really appreciated it. According to historical documents 5 periods are defined in the Library’s history. In the historical sources the first place is occupied by old-printed books of Library collection and 7 Library manuscript catalogues dating from 1745 up to the 1835 which give information about quantity and topical structures of Library collection. The Library is a historical and cultural symbol of the Enlightenment epoch. The Enlightenment and those particular concepts and cultural images pertaining to that epoch had their effect on the formation of Library’s fund. Its main features are as follow: comprehensive nature of the stock, predominance of French eighteenth century editions, presence of academic books and editions on orientalistics as well as works of the ideologues of the Enlightenment and new kinds of literature, which generated as a result of this movement – encyclopaedias, encyclopaedian dictionaries, almanacs, etc. Besides the universal nature of its stock books on history, social and political thought, fiction were dominating. The reconstruction of the history of Vyshnivetsky’s Library, the historical analysis of the provenances in its editions give us better understanding of the personality of its owners and in some cases their philanthropic activities, and a better ability to identify the role of this Library in the culture life of society in a certain epoch.